Commute mode choice dynamics: Accounting for day-to-day variability in longer term change - Chatterjee, Kiron; Clark, Ben; Bartle, Caroline (European Journal of Transport and Infrastructure Research, 2016)
It is of interest to transport policy makers to know whether interventions promoting sustainable transport modes can produce long-term changes in commute mode choices. Recent evidence has shown that a significant minority of commuters are variable in their day-to-day commute mode choices. This suggests that recognition should be given to day-to-day variability in investigating longer term commute behaviour changes. This paper introduces a panel survey that has been specifically designed to capture both day-to-day variability in commuting behaviour and longer term change in commuting behaviour. The analysis of the data accounts for day-to-day variability in commuting behaviour by identifying commute mode choice patterns at the weekly level. It then analyses transitions in commute mode choice patterns over time based on observations at three-monthly intervals. The results show that about one in four commuters mix driving alone to work with using other modes in a typical week and this is more likely for males, those with access to a bicycle and those working in another location during the week and less likely for those who work part-time. Changes in commute mode choices over a three month period are influenced by employment situational characteristics, access to mobility resources, satisfaction with commuting, awareness of sustainable transport measures and changes in life circumstances. Inspection of trajectories for those panel participants who responded to all five waves of the panel indicates that there are more cases of sustained switches between intermediate groups (e.g. car alone commuting to partial car alone commuting) than switches between extreme commuting groups (e.g. car alone commuting to non-car alone commuting). The styles are described in more detail in the remaining of this document.